Analisis Penilaian Pegawai Terbaik Bulanan Di Kantor BPS Kabupaten Kapuas - Safari, Syafruddin; Yani, David Ahmad (Business and Enterpreneurship Journal (BEJ), 2025)
Employee performance appraisal is a crucial element in supporting the achievement of organizational goals, especially within government institutions such as the BPS (Central Statistics Agency) of Kapuas Regency. This study aims to describe the factors influencing the selection of the monthly best employee, the assessment mechanism used, and its impact on employee motivation and performance. This research employs a qualitative descriptive method with a secondary data approach, sourced from internal documents of BPS Kapuas Regency from January to March 2025. Three main indicators used in the evaluation are Employee Performance Achievement Score (CKP), peer voting, and attendance recap or Work Hour Deficiency (KJK). These three indicators are assigned proportional weights (CKP 40%, voting 40%, KJK 20%) in determining the best employee each month. The findings indicate that an evaluation system combining work performance, discipline, and peer assessment can encourage employees to improve their performance and professionalism. However, this system also carries potential risks such as unhealthy competition and bias in peer voting. Therefore, regular evaluations, objective technical guidelines, and assessor training are necessary to ensure the appraisal system remains fair and effective. These findings support the importance of recognition as a form of motivation and a strategy for human resource development in public organizations.